Epitaxial growth and its mechanism of GaN films on nitrided LiGaO2(001) substrates by pulsed laser deposition. Issue 5 (11th December 2014) - Yang, Weijia; Wang, Wenliang; Liu, Zuolian; Lin, Yunhao; Zhou, Shizhong; Qian, Huirong; Li, Guoqiang
Abstract : High-quality GaN films have been grown on nitrided LiGaO2 substrates by pulsed laser deposition. The effect of nitridation on the properties of the GaN films and the growth mechanism of GaN films grown on nitrided LiGaO2 substrates by pulsed laser deposition have also been systemically studied. Abstract : High-quality GaN films have been grown on nitrided LiGaO2 substrates by pulsed laser deposition with an in-plane epitaxial relationship of GaN[11−20]//LiGaO2 [010]. The surface morphologies and structural properties of the as-grown GaN films are studied in detail by various characterization methods. These characterizations for the as-grown GaN films show excellent crystalline quality with a full-width at half-maximum value of 0.1° and a very smooth surface with a surface root-mean-square roughness of 1.1 nm. There is an interfacial layer existing between GaN films and LiGaO2 substrates with a thickness of 0.9 nm. Furthermore, the nitridation effect on the properties of GaN films and the growth mechanism of GaN films on nitrided LiGaO2 substrates by pulsed laser deposition have also been systemically studied. This work opens up a broad prospect for the growth of high-efficiency GaN-based devices on LiGaO2 (001) substrates.